DIRECTIONS FOR USING THE EXPERIENCE OF FOREIGN COUNTRIES IN APPLYING TAX INCENTIVES (American Journal of Business Management, Economics and Banking, 2025)
This article describes the theoretical issues of taxing the activities of enterprises, directions for encouraging their activities through the tax mechanism, and the international experience of providing tax incentives in the tax system of some foreign countries. The international norms and mechanisms used to encourage the activities of enterprises through tax incentives are cited. As a result of the analysis, scientific conclusions were obtained on the prospects of using foreign countries' best practices in stimulating enterprises' activities.